Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

Traditional and digital examination of the baculum of a leopard seal ( Hydrurga leptonyx ) - James P. Rule; Hazel L. Richards; Tahlia I. Pollock; David P. Hocking; Alistair R. Evans (Marine Mammal Science, 2024)

Shelf break exchange processes influence the availability of the northern shortfin squid, Illex illecebrosus , in the Northwest Atlantic - Sarah L. Salois; Kimberly J. W. Hyde; Adrienne Silver; Brooke A. Lowman; Avijit Gangopadhyay; Glen Gawarkiewicz; Anna J. M. Mercer; John P. Manderson; Sarah K. Gaichas; Daniel J. Hocking; Benjamin Galuardi; Andrew W. Jones; et al. (Fisheries Oceanography, 2023)
The United States Northern Shortfin squid fishery is known for its large fluctuations in catch at annual scales. In the last 5 years, this fishery has experienced increased availability of Illex illecebrosus along the Northeast US continental shelf (NES), resulting in high catch per unit effort (CPUE) and early fishery closures due to quota exceedance. The fishery occurs within the Northwest Atlantic, whose complex dynamics are set up by the interplay between the large‐scale Gulf Stream, mesoscale eddies, Shelfbreak Jet, and shelf‐slope exchange processes. Our ability to understand and quantify this regional variability is requisite for understanding the availability patterns of Illex , which are largely influenced by oceanographic conditions. In an effort to advance our current understanding of the seasonal and interannual variability in this species' relative abundance on the NES, we used generalized additive models to examine the relationships between the physical environment and hotspots of productivity to changes in CPUE of I. illecebrosus in the Southern stock component, which comprises the US fishery. Specifically, we derived oceanographic indicators by pairing high‐resolution remote sensing data and global ocean reanalysis physical data to high‐resolution fishery catch data. We identified a suite of environmental covariates that were strongly related to instances of higher catch rates. In particular, bottom temperature, warm core rings, subsurface features, and frontal dynamics together serve as indicators of habitat condition and primary productivity hotspots, providing great utility for understanding the distribution of Illex with the potential for forecasting seasonal and interannual availability.

Establishing the Signal above the Noise: Accounting for an Environmental Background in the Detection and Quantification of Salmonid Environmental DNA - Morgan D. Hocking; Jeffrey C. MacAdams; Michael J. Allison; Lauren C. Bergman; Robert Sneiderman; Ben F. Koop; Brian M. Starzomski; Mary L. Lesperance; Caren C. Helbing (Fishes, 2022)
A current challenge for environmental DNA (eDNA) applications is how to account for an environmental (or false-positive) background in surveys. We performed two controlled experiments in the Goldstream Hatchery in British Columbia using a validated coho salmon (Oncorhynchus kisutch) eDNA assay (eONKI4). In the density experiment at high copy number, eDNA in 2 L water samples was measured from four 10 kL tanks containing 1 to 65 juvenile coho salmon. At these densities, we obtained a strong positive 1:1 relationship between predicted copy number/L and coho salmon biomass (g/L). The dilution experiment simulated a situation where fish leave a pool environment, and water from upstream continues to flow through at rates of 141–159 L/min. Here, three coho salmon were placed in four 10 kL tanks, removed after nine days, and the amount of remaining eDNA was measured at times coinciding with dilutions of 20, 40, 80, 160, and 1000 kL. The dilution experiment demonstrates a novel method using Binomial–Poisson distributions to detect target species eDNA at low copy number in the presence of an environmental background. This includes determination of the limit of blank with background (LOB-B) with a controlled false positive rate, and limit of detection with background (LOD-B) with a controlled false negative rate, which provides a statistically robust “Detect” or “No Detect” assessment for eDNA surveys.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Dynamics and predicted distribution of an irrupting ‘sleeper’ population: fallow deer in Tasmania - Calum X. Cunningham; George L. W. Perry; David M. J. S. Bowman; David M. Forsyth; Michael M. Driessen; Matt Appleby; Barry W. Brook; Greg Hocking; Jessie C. Buettel; Ben J. French; Rowena Hamer; Sally L. Bryant; et al. (Biological Invasions, 2022)

Demographic effects of phenological variation in natural populations of two pond-breeding salamanders - Thomas L. Anderson; Julia E. Earl; Daniel J. Hocking; Michael S. Osbourn; Tracy A. G. Rittenhouse; Jarrett R. Johnson (Oecologia, 2021)

Abundance and phenology patterns of two pond-breeding salamanders determine species interactions in natural populations - Thomas L. Anderson; Daniel J. Hocking; Christopher A. Conner; Julia E. Earl; Elizabeth B. Harper; Michael S. Osbourn; William E. Peterman; Tracy A. G. Rittenhouse; Raymond D. Semlitsch (Oecologia, 2015)

Influence of agricultural upland habitat type on larval anuran assemblages in seasonally inundated wetlands - Kimberly J. Babbitt; Matthew J. Baber; Daniel L. Childers; Daniel Hocking (Wetlands, 2009)

Gait function in adults with Williams syndrome - Darren R. Hocking; Nicole J. Rinehart; Jennifer L. McGinley; John L. Bradshaw (Experimental Brain Research, 2009)

Utility of Microsatellite Markers and Amplified Fragment Length Polymorphism in the Study of Potentially Ochratoxigenic Black Aspergilli - Alexandre Esteban; Su-lin L. Leong; Ailsa D. Hocking; M. Lourdes Abarca; F. Javier Cabañes; Nai Tran-Dinh (Current Microbiology, 2008)

Evaluation of physiological traits for improving drought tolerance in faba bean (Vicia faba L.) - Habib ur Rahman Khan; W. Link; T. J. Hocking; F. L. Stoddard (Plant and Soil, 2007)